2017
DOI: 10.2217/pgs-2016-0204
|View full text |Cite
|
Sign up to set email alerts
|

Replicated Evidence for Aminoacylase 3 and Nephrin Gene Variations to Predict Antihypertensive Drug Responses

Abstract: We provide support for two pharmacogenomic markers for beta-blockers and angiotensin receptor antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…No metabolite in placebo plasma samples was shown to associate with an antihypertensive drug response at statistical significance level of P < 2 x 10 −5 . The potential association of baseline levels of aromatic amino acids, phenylalanine and N-acetylphenylalanine in particular, as already reported by us [ 42 ], to a favorable response to bisoprolol is of some interest due to our previous findings of association between ACY3 (coding for aminoacylase 3) variation and bisoprolol responsiveness [ 13 ]; aminoacylase 3 is the enzyme catalyzing conversion of N-acetylphenylalanine to phenylalanine. It is of note that while the levels of a number of long-chain acylcarnitines were diminished in a relatively systematic fashion by amlodipine, bisoprolol and losartan, their baseline levels were not predictive for a good antihypertensive response to any of these drugs.…”
Section: Discussionmentioning
confidence: 78%
“…No metabolite in placebo plasma samples was shown to associate with an antihypertensive drug response at statistical significance level of P < 2 x 10 −5 . The potential association of baseline levels of aromatic amino acids, phenylalanine and N-acetylphenylalanine in particular, as already reported by us [ 42 ], to a favorable response to bisoprolol is of some interest due to our previous findings of association between ACY3 (coding for aminoacylase 3) variation and bisoprolol responsiveness [ 13 ]; aminoacylase 3 is the enzyme catalyzing conversion of N-acetylphenylalanine to phenylalanine. It is of note that while the levels of a number of long-chain acylcarnitines were diminished in a relatively systematic fashion by amlodipine, bisoprolol and losartan, their baseline levels were not predictive for a good antihypertensive response to any of these drugs.…”
Section: Discussionmentioning
confidence: 78%
“…S4 online). A pharmacogenetic substudy was done in Scandinavia, including 1,146 Finnish patients whose DNA samples were available for GWAS 20 . Of this group, a total of 401 patients on monotherapy at 2 months' visit (losartan, n = 200; atenolol, n = 201) were selected for analysis of BP responses in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, an intriguing finding from the GENRES study of in Finnish men randomized to several different antihypertensive drugs found in an unbiased genome analysis that carriers of a C allele at rs3814995 had greater BP response to losartan [47]. This class effect was replicated in American and European cohorts, and also in a separate analysis of Finnish patients in the LIFE (Losartan Intervention For Endpoint reduction in Hypertension) trial [48]. rs3814995 is a SNP within NPHS1, where the A allele codes for a missense mutation from glutamine to lysine at amino acid 117 in nephrin, a crucial protein in the glomerular slit diaphragm.…”
Section: Inhibitors Of the Renin-angiotensin Systemmentioning
confidence: 90%